Diffusion tensor imaging predicts cognitive function change following partial brain radiotherapy for low-grade and benign tumors. Issue 2 (August 2016) - Chapman, Christopher H.; Zhu, Tong; Nazem-Zadeh, Mohamad; Tao, Yebin; Buchtel, Henry A.; Tsien, Christina I.; Lawrence, Theodore S.; Cao, Yue
Abstract: Purpose/objectives: Radiation injury to parahippocampal cingulum white matter is associated with cognitive decline. Diffusion tensor imaging (DTI) detects micropathologic changes in white matter. Increased radial diffusion (RD) and decreased axial diffusion (AD) correspond to demyelination and axonal degeneration/gliosis respectively. We aimed to develop a predictive model for radiation-induced cognitive changes based upon DTI changes. Materials/methods: Twenty-seven adults with benign or low-grade tumors received partial brain radiation therapy (RT) to a median dose of 54 Gy. Patients underwent DTI before RT, during RT, and at the end of RT. Cognitive testing was performed before RT, and 6 and 18 months after RT. Parahippocampal cingulum white matter was contoured to obtain mean values of AD and RD. Results: By univariate analysis, decreasing AD and increasing RD during RT predicted declines in verbal memory and verbal fluency. By multivariate analysis, baseline neurocognitive score was the only clinical variable predicting verbal memory change; no clinical variables predicted verbal fluency change. In a multivariate model, increased RD at the end of RT significantly predicted decline in verbal fluency 18 months after RT. Conclusions: Imaging biomarkers of white matter injury contributed to predictive models of cognitive function change after RT.